2010
DOI: 10.1080/00150191003748972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BNT Addition on the Microstructure and PTC Properties of La-Doped BaTiO3-Based PTCR Ceramics

Abstract: Lanthanum (La) doped BaTiO 3 -(Bi 0.5 Na 0.5 )TiO 3 (BT-BNT) positive temperature coefficient of resistivity (PTCR) ceramics were prepared by a conventional solid state reaction method. The microstructure and PTCR effect of BT-BNT ceramics were investigated by scanning electron microscopy and measurement of resistivity-temperature dependence. The BT-BNT ceramics sintered in a N 2 gas flow possessed low room-temperature resistivity (ρ RT < 10 2 ·cm) and PTCR effect wasn't remarkable (ρ max /ρ min < 10); through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The grains were well formed and the grain boundaries were clear-cut. It can be clearly seen that the average grain size decreased from 8.1 to 3.9 lm with the increase of BNT content which was generally in agreement with previous results [22]. And the grain growth was also inhibited by the incorporation of BaBiO 3 .…”
Section: Influence Of Bnt Concentrationsupporting
confidence: 92%
“…The grains were well formed and the grain boundaries were clear-cut. It can be clearly seen that the average grain size decreased from 8.1 to 3.9 lm with the increase of BNT content which was generally in agreement with previous results [22]. And the grain growth was also inhibited by the incorporation of BaBiO 3 .…”
Section: Influence Of Bnt Concentrationsupporting
confidence: 92%
“…The density of the sintered samples, with different atomic concentrations of La (0, 0.003, 0.007, 0.01, 0.013, 0.033, and 0.067) was determined by the Archimedes method. The results presented in Table 1 A similar effect of grain size reduction has also been observed in other ferroelectric systems in addition to BNT, such as in the case of BaTiO3 and PZT [25][26][27]. The effect of La doping in the A sites of the BNT perovskite structure, substituting Na and Bi, leads to a decrease in grain size, and for higher concentrations, it is expected also that it contributes to the appearance of an additional phases [25][26][27].…”
Section: Microstructural Analysessupporting
confidence: 79%
“…2 show an evolution that allows identifying the presence of a mixture of crystalline phases, rhombohedral (R3c) and cubic (Pm-3m group). Previous studies about La-doping into perovskite structures have suggested that La 3+ replaces preferably A-sites due to their close radii [25,27]. D. Shannon [30] reports the next ionic radius for Na + (rNa=1.39Å, CN=12), La 3+ (rLa=1.36Å, CN=12) and for Bi 3+ only gives ionic radii for coordination 8, Bi 3+ (rBi=1.17 CN=8).…”
Section: X-ray Diffraction Resultsmentioning
confidence: 94%